Evaluasi Bantuan Pupuk Organik Cair Untuk Produktivitas Padi Dan Pendapatan Petani Di Ponorogo - Sudaryanto Sudaryanto (Manajemen Agribisnis: Jurnal Agribisnis, 2020)
The Government of Ponorogo Regency through the Department of Agriculture and Fisheries of Ponorogo Regency rolled out a liquid organic fertilizer (POC) assistance program for farmer groups. This study aims to evaluate the aid program based on an analysis of the incentives obtained by farmers through rice productivity, farmers' income and their perception of the liquid organic fertilizer (POC) assistance program. The study was conducted in a sample area in POC beneficiary groups in 2017 and 2018 with a total sample of 30 farmer groups. Sampling uses proposive sampling, and the data are analyzed using analysis of farming, analysis of production factors and analysis of farmers' perceptions. The amount of assistance was 6.5 lt per hectare. The results showed an increase in rice productivity by 1,051 kg / ha. The income of farmer groups has increased by Rp. 3,255,483 per Ha. As many as 80% of respondents stated that POC was able to increase crop productivity and 93.33% stated there was no negative impact from the use of POC. Problems that often occur in the implementation of POC assistance programs encountered include: lack of aid volume (20%), lack of understanding of the application (6.67%). The hope is that the volume of assistance will be increased (36.67%), timely assistance (26.22%) and staff assistance will be intensified (16.67%). Key words: Liquid organic fertilizer, productivity, economic aspects, environmentally friendly.